PHYSİCAL ACTİVİTY AND FRAGİLİTY LEVELS İN ELDERLY İNDİVİDUALS - ANDI, Senem; AKÇOBAN, Sümeyye; GÜNGÖR, Serap (Göbeklitepe Medical Science Journal, 2022)
This study was conducted to determine the physical activity and fragility levels of elderly individuals. This study was conducted between October 4, 2021, and December 4, 2021, with 216 elderly individuals in descriptive and cross-sectional type. "Individual Over 65 Descriptive Information Form", "Edmonton Vulnerability Scale" and "International Physical Activity Questionnaire" were used as data collection forms. Data were collected through face-to-face interview. Data analysis was done in SPSS 25.0 package program. A p<0.05 value was accepted for statistical significance. The mean age of the elderly individuals was 71.56±6.10 years, 54.6% were female, 72.2% were married, and 40.3% were primary school graduates. It was determined that 42.1% of the elderly individuals were not frail, and the mean frailty score was 5.41±2.59. It was determined that 52.8% of the individuals performed moderate physical activity in the International Physical Activity Questionnaire Average Scores, and they performed the most walking activity among the total physical activity. In addition, a statistically significant difference was found between gender, educational status, marital status, having a chronic disease, and frailty. A statistically significant difference was found between physical activity level and marital status, educational status and living with family members. Elderly individuals were found to have varying degrees of fragility and to do moderate physical activity.